An investigation on Graphical Abstracts use in scholarly articles. Issue 1 (February 2017) - Yoon, JungWon; Chung, EunKyung
Graphical abstract: Highlights: From 2011 to 2015, a 350% increase of graphical abstracts use is revealed in social sciences journals. 50% of graphical abstracts are simply duplicated from the manuscript's existing visual components. Contents of graphical abstracts vary: overview, results, methods, and background. Different types of visualizations are used depending on the contents of graphical abstracts. Abstract: Recently, Graphical Abstracts (GA) are increasingly being used in scholarly articles in order to enhance browsing and aid in paper selection. This study aims to demonstrate how GAs have been adopted in the social sciences. In the social sciences, GAs appeared for the first time in 2010, and from 2011 to 2015 a 350% increase was observed. Forty-seven percent of journals related to the social sciences have published at least one article with a GA. Among the social science disciplines, social and economic geography has most actively adopted GAs, whereas, in law, GAs are still not used. Authors use GAs to present: 1) an overview of the article, including the research process and key results (sometimes with background), 2) the key results of the study, 3) the research process or methods used, and 4) the background of the study. Authors re-use the visualizations in their manuscripts, integrate or modify the visualizations in their manuscripts, or create a new visualization for the GA. Depending on the content of GAs, different types of visualizations are used; for example, charts are mainly used to represent results and diagrams are used to present research methods or provide an overview of the article. Areas of future research into GAs are suggested.